Servant Leadership: Son of Man as Minister and Life Giver in Mark 10.45 - Kgatle, Mookgo Solomon (Journal of pentecostal theology, 2017)
This article discusses the Son of Man as Minister and Life giver in Mk 10.45. The Son of Man as Minister is the servant who did not come on earth to be ministered to but to minister to others. The Son of Man as the Life giver is the servant who pays a price for the sake of many sinners in the world. The life, crucifixion, death, and resurrection of the Son of Man become that price for the release of those who are enslaved by sin. The purpose of this article is to demonstrate that these aspects of the Son of Man – Minister and Life giver – are aspects of servant leadership.